A model for genesis of transcription systems. Issue 1 (1st January 2016) - Burton, Zachary F.; Opron, Kristopher; Wei, Guowei; Geiger, James H.
ABSTRACT: Repeating sequences generated from RNA gene fusions/ligations dominate ancient life, indicating central importance of building structural complexity in evolving biological systems. A simple and coherent story of life on earth is told from tracking repeating motifs that generate α/β proteins, 2-double-Ψ−β-barrel (DPBB) type RNA polymerases (RNAPs), general transcription factors (GTFs), and promoters. A general rule that emerges is that biological complexity that arises through generation of repeats is often bounded by solubility and closure (i.e., to form a pseudo-dimer or a barrel). Because the first DNA genomes were replicated by DNA template-dependent RNA synthesis followed by RNA template-dependent DNA synthesis via reverse transcriptase, the first DNA replication origins were initially 2-DPBB type RNAP promoters. A simplifying model for evolution of promoters/replication origins via repetition of core promoter elements is proposed. The model can explain why Pribnow boxes in bacterial transcription (i.e., −12 TATAATG −6 ) so closely resemble TATA boxes (i.e., −31 TATAAAAG −24 ) in archaeal/eukaryotic transcription. The evolution of anchor DNA sequences in bacterial (i.e., −35 TTGACA −30 ) and archaeal (BREup ; BRE for TFB recognition element) promoters is potentially explained. The evolution of BREdown elements of archaeal promoters is potentially explained.